Differential Discrimination against Mobile EU Citizens: Experimental Evidence from Bureaucratic Choice Settings - Adam, Christian; Fernández-i-Marín, Xavier; James, Oliver; Manatschal, Anita; Rapp, Carolin; Thomann, Eva (My University, 2021)
EU citizens have rights when living in a member state other than their own. Bureaucratic discrimination undermines the operation of these rights. We go beyond extant research on bureaucratic discrimination in two ways. First, we move beyond considering mobile EU citizens as homogenous immigrant minority to assess whether EU citizens from certain countries face greater discrimination than others. Second, we analyse whether discrimination patterns vary between the general population and public administrators regarding attributes triggering discrimination and whether accountability prevents discrimination. In a pre-registered design, we conduct a population-based conjoint experiment in Germany including a sub-sample of public administrators. We find that (1) Dutch and fluent German speakers are preferred, i.e. positively discriminated, over Romanians and EU citizens with broken language skills, that (2) our way of holding people accountable was ineffective, and that (3) in all these regards discriminatory behaviour of public administrators is similar to the general population.
Keywords: Accountability; Conjoint experiment; Discrimination; EU citizenship; Street-level bureaucracy